Pediatric all-terrain vehicle (ATV) injuries: An epidemic of cost and grief - Kent A. Strohecker; Christian J. Gaffney; Jove Graham; Kaan Irgit; Wade R. Smith; Thomas R. Bowen (Acta Orthopaedica et Traumatologica Turcica, 2017)
Objective: Evaluate cost of care of all-terrain vehicle (ATV) related injuries sustained by riders 16 years and younger in Pennsylvania. Methods: Population-based retrospective cohort design reviewing costs of care of 78 patients (≤16 years), admitted (01/01/2007–12/31/2009) to our institution for injuries sustained during an ATV accident. Results: Cost of care varied from $322 to $310,435. Mean and median costs for all patients were $25,760 and $8,066, respectively. Average costs increased with increasing age. Patients wearing helmets or driving the ATV had lower mean costs, but these trends were not statistically significant. Crashes with stationary objects not involving rollover or ejection had significantly lower mean costs than other crash types (p = 0.01). Patients involved in rollover accidents were significantly more likely to require an overnight hospital stay (OR = 3.45, p = 0.02). Patients wearing helmets were marginally less likely to require an overnight admission (OR = 0.34, p = 0.07). Conclusion: ATV crashes involving unhelmeted riders and rollover accidents result in significant medical costs. Interventions to increase helmet use and measures to improve stability are likely to reduce these costs and shorten hospital stays. Level of evidence: Level IV, Economic study. Keywords: Pediatric, all-terrain vehicle injury, Epidemic cost